Evaluation of different recall periods for the US National Cancer Institute's PRO-CTCAE. (June 2017) - Mendoza, Tito R; Dueck, Amylou C; Bennett, Antonia V; Mitchell, Sandra A; Reeve, Bryce B; Atkinson, Thomas M; Li, Yuelin; Castro, Kathleen M; Denicoff, Andrea; Rogak, Lauren J; Piekarz, Richard L; Cleeland, Charles S; et al.
Aims: The US National Cancer Institute recently developed the PRO-CTCAE (Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events). PRO-CTCAE is a library of questions for clinical trial participants to self-report symptomatic adverse events (e.g. nausea). The objective of this study is to inform evidence-based selection of a recall period when PRO-CTCAE is included in a trial. We evaluated differences between 1-, 2-, 3-, and 4-week recall periods, using daily reporting as the reference. Methods: English-speaking patients with cancer receiving chemotherapy and/or radiotherapy were enrolled at four US cancer centers and affiliated community clinics. Participants completed 27 PRO-CTCAE items electronically daily for 28 days, and then weekly over 4 weeks, using 1-, 2-, 3-, and 4-week recall periods. For each recall period, mean differences, effect sizes, and intraclass correlation coefficients were calculated to evaluate agreement between the maximum of daily ratings and the corresponding ratings obtained using longer recall periods (e.g. maximum of daily scores over 7 days vs 1-week recall). Analyses were repeated using the average of daily scores within each recall period rather than the maximum of daily scores. Results: A total of 127 subjects completed questionnaires (57% male; median age: 57). The median of the 27 mean differences in scores on the PRO-CTCAE 5-point response scale comparing the maximum daily versus the longer recall period (and corresponding effect size) was −0.20 (−0.20) for 1-week recall, −0.36 (−0.31) for 2-week recall, −0.45 (−0.39) for 3-week recall, and −0.47 (−0.40) for 4-week recall. The median intraclass correlation across 27 items between the maximum of daily ratings and the corresponding longer recall ratings for 1-week recall was 0.70 (range: 0.54–0.82), for 2-week recall was 0.74 (range: 0.58–0.83), for 3-week recall was 0.72 (range: 0.61–0.84), and for 4-week recall was 0.72 (range: 0.64–0.86). Similar results were observed for all analyses using the average of daily scores rather than the maximum of daily scores. Conclusion: A 1-week recall corresponds best to daily reporting. Although intraclass correlations remain stable over time, there are small but progressively larger differences between daily and longer recall periods at 2, 3, and 4 weeks, respectively. The preferred recall period for the PRO-CTCAE is the past 7 days, although investigators may opt for recall periods of 2, 3, or 4 weeks with an understanding that there may be some information loss.